The Asymmetries of a Small World: Entry Into and Withdrawal From International Markets by French Firms - Dirk Engel; Vivien Procher; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper studies the internationalization behaviour of French companies, using more than 330.000 observations for three two-year intervals. We analyze the role of productivity, organisational and ownership structure, and of financial characteristics for the decision to enter into and exit from foreign markets. High levels of productivity are documented to be characteristic of companies deciding to engage in exporting or foreign direct investment (FDI). However, there does not seem to be a significant correlation between productivity and divestment decisions. Moreover, companies with corporate shareholders are more likely to intensify their international engagement and to retain their cross-border activities. Finally, with some exceptions high levels of short-term and long-term debt tend to make entry into a more intense international engagement more and its reduction less likely. – – Der Artikel untersucht das Internationalisierungsverhalten französischer Firmen mit Hinblick auf den Einfluss von Produktivität, Eigentümer- und Kapitalstruktur auf die Markteintritts- und Marktaustrittsentscheidungen im Ausland. Firmen, die in Märkte eintreten, entweder über Exporte oder ausländische Direktinvestitionen, weisen schon im Vorfeld ein höheres Produktivitätsniveau auf. Im Gegensatz dazu gibt es keine Hinweise auf eine Korrelation zwischen Firmenproduktivität und Marktaustrittsentscheidungen. Mit Bezug auf die Eigentümerstruktur entscheiden sich insbesondere französische Firmen mit strategischen Investoren in ausländische Märkte einzutreten und diese längerfristig zu bedienen. Im Allgemeinen scheint ein höheres Schuldenniveau zu einem erhöhten Markteintritt und verminderten Marktaustritt zu frühen.
Keywords: F23; D21; L21; C25; 330; Foreign markets; entry and exit; exporting; FDI; Multinationales Unternehmen; Internationale Markteintrittsstrategie; Direktinvestition; Desinvestition; Außenhandelswirtschaft; Produktivität; Eigentümerstruktur; Frankreich